Establishing Legal Certainty in the Digital Era: Challenges and Solutions - Rahman Toyi, Abdul; Zachra Putri Hamidun, Elmira (Universitas Negeri Gorontalo, 2025)
This article aims to examine the challenges and formulate solutions in building legal certainty in the digital era in Indonesia. This writing uses a normative legal method with a legislative, conceptual, and comparative case study approach. The analysis shows that the rapid development of digital technology has revealed various legal challenges, such as inconsistencies in regulations before the enactment of the Personal Data Protection Law, the lag of legislation compared to technological innovation, fragmentation of authority between institutions, the dilemma between encouraging innovation and protecting individual rights, and the complexity of jurisdiction in international cyber law. To answer these challenges, comprehensive legal reform is needed, the establishment of an independent institution for personal data protection, regulatory harmonization, and strengthening international cooperation. Furthermore, the concept of Agile Lawmaking, the implementation of Legal Tech and Smart Contracts, and digital legal education reform are the keys to building an adaptive and responsive legal system, as demonstrated by best practices from Estonia and Singapore. As a recommendation, it is necessary to immediately update regulations based on real-time data, develop a national digital legal ecosystem, increase the capacity of legal officers, and actively involve the community in formulating policies to ensure legal certainty while encouraging sustainable digital economic growth.